Protective Effects of Imidapril on He-Ne Laser-Induced Thrombosis in Cerebral Blood Vessels of Stroke-Prone Spontaneously Hypertensive Rats - Sasaki, Yasuto; Noguchi, Takanori; Seki, Junji; Giddings, J. C.; Yamamoto, Junichiro (Thrombosis and Haemostasis, 2000)
Inhibitors of angiotensin converting enzyme (ACE) have been developed recently for therapeutic purposes in hypertension and ischemic cardiovascular diseases. Ogiku et al. (1) reported that one such inhibitor, imidapril, significantly prolonged survival in stroke-prone spontaneously hypertensive rats (SHRSP). The present study was designed to investigate the effect of imidapril on cerebral blood vessels in SHRSP to clarify role of the ACE inhibitor in mechanisms of cerebral thrombosis and stroke. Imidapril was administered orally at 1.0 and 5.0 mg/kg/day for 3 weeks from the age of 7 weeks, and was shown to prevent the usual increase in blood pressure seen in these animals. It also delayed He-Ne laser-induced cerebral thrombosis and increased significantly the plasma concentration of nitric oxide metabolites (NO2/NO3). To confirm the association between nitric oxide (NO) and these effects of imidapril, an inhibitor of nitric oxide synthase, NG- nitro-L-arginine methyl ester hydrochloride (L-NAME) was dissolved in drinking water and administered to the animals for 3 weeks. Four of six rats died from stroke when L-NAME was given alone. When imidapril (5.0 mg/kg/day) was administered with L-NAME, however, the animals showed no signs or symptoms of stroke. In these instances, therefore, the concurrent administration of L-NAME with imidapril reversed significantly the effects of imidapril. Intravenous injection of imidaprilat (100 µg/kg), an active metabolite of imidapril, also decreased blood pressure significantly and increased the plasma levels of NO2/NO3 after 5 min. Moreover, imidaprilat enlarged arteriolar diameters and caused an increase in red cell velocity and mean blood flow in pial arterioles after 15 min.The results strongly suggested that imidapril protects cerebral vessels in SHRSP by elevating the release of NO, thereby improving the cerebral circulation and reducing the tendency to thrombosis and stroke.
Keywords: ACE-inhibitor; imidapril; thrombosis; nitric oxide; pial vessel